Concomitant Alopecia Areata and Profound Bone Marrow Suppression: An Unusual Manifestation of Azathioprine Toxicity - Debdeep Mitra; Anuj Bhatnagar; PK Sanoj; Rohit Kothari; Krishna Talukdar; Arun Singh (Clinical Dermatology Review)
Azathioprine is an immunosuppressive purine analog commonly utilized in dermatology as a steroid-sparing agent to manage a wide array of chronic inflammatory and autoimmune skin disorders. Its efficacy has been demonstrated in conditions such as atopic dermatitis, chronic urticaria, and autoimmune blistering diseases. The drug's therapeutic mechanism centers on its ability to interfere with DNA synthesis in proliferating lymphocytes, thereby exerting cytotoxic effects. However, its use is not without significant risks, particularly hematological complications, with myelosuppression being a well-recognized adverse event. While mild to moderate bone marrow suppression is relatively common, severe pancytopenia remains an infrequent but potentially life-threatening occurrence. Cutaneous adverse effects of azathioprine are diverse and range from hypersensitivity reactions to malignancies. Hair loss, particularly of the telogen effluvium type, has been reported during prolonged treatment courses, often associated with cumulative cytotoxic effects or nutritional deficiencies secondary to chronic immunosuppression. However, the abrupt onset of alopecia areata (AA) during azathioprine therapy is exceedingly rare. AA is an autoimmune-mediated, non-scarring hair loss condition characterized by T-cell infiltration around hair follicles, resulting in localized or generalized hair shedding. The emergence of AA in the context of azathioprine use raises questions regarding the paradoxical activation of autoimmune pathways in an otherwise immunocompromised host. In this report, we describe a clinically unusual and complex case of a patient with chronic spontaneous urticaria, accompanied by elevated serum immunoglobulin E levels, who developed sudden-onset, rapidly progressing alopecia areata concurrent with azathioprine-induced bone marrow suppression. Histopathological examination confirmed AA, differentiating it from nonspecific hair loss secondary to cytotoxicity. Interestingly, the patient's condition improved following discontinuation of azathioprine, with concurrent resolution of leukopenia and gradual hair regrowth, suggesting a temporal and possibly causative relationship between the drug and both the hematologic and dermatologic manifestations. This case underscores the unpredictable nature of immunomodulatory therapy and highlights a paradox wherein a drug intended to suppress autoimmune activity potentially triggers a separate autoimmune condition. It also emphasizes the importance of vigilant monitoring for both common and rare adverse effects during azathioprine therapy. Such observations broaden our understanding of drug-induced autoimmune phenomena and underscore the need for individualized therapeutic approaches in complex dermatological cases.